2015
DOI: 10.1007/s12017-015-8359-5
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Normal Cerebral Oxygen Consumption with Rapamycin Treatment in a Rat Model of Autism–Tuberous Sclerosis

Abstract: Tuberous sclerosis (TSC) is associated with autism spectrum disorders and has been linked to metabolic dysfunction and unrestrained signaling of the mammalian target of rapamycin (mTOR). Inhibition of mTOR by rapamycin can mitigate some of the phenotypic abnormalities associated with TSC and autism, but whether this is due to the mTOR-related function in energy metabolism remains to be elucidated. In young Eker rats, an animal model of TSC and autism, which harbors a germ line heterozygous Tsc2 mutation, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…As described previously (Chi et al, 2015 ; Weiss et al, 2007 , 2009 ), this study was conducted following the guidelines set forth by the US Public Health Service, as outlined in the Guide for the Care of Laboratory Animals (DHHS Publication No. 85-23, revised 1996), and received approval from our Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As described previously (Chi et al, 2015 ; Weiss et al, 2007 , 2009 ), this study was conducted following the guidelines set forth by the US Public Health Service, as outlined in the Guide for the Care of Laboratory Animals (DHHS Publication No. 85-23, revised 1996), and received approval from our Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…As we described previously (Chi et al, 2015 ), the rats were anesthetized with a 2% isoflurane-air-oxygen mixture via tracheal tube and mechanical ventilation to maintain arterial PO 2 above 100 mm Hg and PCO 2 around 35 mmHg. A femoral artery and a femoral vein cannulation were performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed earlier, tuberous sclerosis complex models had increased hippocampal neuron volume, blood flow, and oxygen consumption. Correspondingly, the administration of rapamycin has been reported to lower cerebral blood flow and oxygen consumption in hippocampal regions of the Tsc2 mutant rat, potentially by downregulating Akt signals ( 146 ). This also accords with previous observations, which showed that pharmacological inhibition of mTORC suppressed granule cell hypertrophy in Pten mutant mice ( 258 ) and inhibited the PI3K/AKT/mTOR signaling pathway in VPA-induced rats ( 220 ).…”
Section: Therapies That Positively Influence the Structure And Functi...mentioning
confidence: 99%